HER+ Final report Ethiopia - Endrias, Abrhame; Ketema, Dessalegn; Nchanji, Eileen; Zewdie, Yidnekachew; Roothaert, Ralf; Jaleta, Gemechis (CGIAR Initiative on Gender Equality, 2024)
Green Agro-Solution PLC has collaborated with the Alliance of Bioversity International and CIAT, the World Veg Center, and SNV to offer agricultural services enhanced by digital technologies for Vegetable Business Networks (VBNs) groups in the Welmera and Ejere woredas of the West Showa zone. This report provides an overview of the initiative's major accomplishments for off-takers and farmers.